El peso mexicano: la gestión de cobertura del riesgo cambiario mediante la teoría de los efectos olvidados - Salazar Garza, Ricardo (2012)
This paper is about developing a nonlinear model to predict the behavior of future exchange rate based on the opinion of the economic agents participating in the dollar/peso market. Such views are treated with Fuzzy Logic and a variant of it, known as the Theory of Forgotten Effects. The aim is to find a mechanism for making coverage decisions that allow us an optimal exchange rate risk management at a lower cost than that which involves operations with traditional hedging instruments. For the period of investigation and applying this model, the results support that the collective opinions of economic experts involved in the decision making risk management of exchange rate provide better results than those using traditional methods in the future markets